The Glutamate–Glutamine (GABA) Cycle: Importance of Late Postnatal Development and Potential Reciprocal Interactions between Biosynthesis and Degradation - Hertz, Leif (Frontiers in Endocrinology, 2013)
The gold standard for studies of glutamate-glutamine(GABA) cycling and its connections to brain biosynthesis from glucose of glutamate and GABA and their subsequent metabolism are the elegant in vivo studies by 13C magnetic resonance spectroscopy (NMR), showing the large fluxes in the cycle. However, simpler experiments in intact brain tissue (e.g. immunohistochemistry), brain slices, cultured brain cells and mitochondria have also made important contributions to the understanding of details, mechanisms and functional consequences of glutamate/GABA biosynthesis and degradation. The purpose of this review is to attempt to integrate evidence from different sources regarding i) the enzyme(s) responsible for the initial conversion of -ketoglutarate to glutamate; ii) the possibility that especially glutamate oxidation is essentially confined to astrocytes; and iii) the ontogenetically very late onset and maturation of glutamine-glutamate(GABA) cycle function. Pathway models based on the functional importance of aspartate for glutamate synthesis suggest the possibility of interacting pathways for biosynthesis and degradation of glutamate and GABA and the use of transamination as the default mechanism for initiation of glutamate oxidation. The late development and maturation are related to the late cortical gliogenesis and convert brain cortical function from being purely neuronal to becoming neuronal-astrocytic. This conversion is associated with huge increases in energy demand and production, and the character of potentially incurred gains of function are discussed. These may include alterations in learning mechanisms, in mice indicated by lack of pairing of odor learning with aversive stimuli in newborn animals but the development of such an association 10-12 days later. The possibility is suggested that analogous maturational changes may contribute to differences in the way learning is accomplished in the newborn human brain and during later development.